BACKWARD PRODUCTION OF A SPIN-PARITY 1+ K RHO RESONANCE AT 1.28 GEV - Gavillet, P; Diaz, J; Dionisi, C; Gurtu, A; Hemingway, R; Losty, M; Marin, J; Mazzucato, M; Montanet, L; Pagiola, E; Blokzijl, R; Jongejans, B; et al. (1978)
A (Kππ)+ mass enhancement is observed in the reactions K-p → Ξ -Ko+π+πo- when events with a small (K- → Ξ-) four momentum transfer squared are selected. The signal is also visible in the reaction K-p → Ξ-π++ neutrals. The enhancement, centered at 1.28 GeV, is seen to decay preferentially into Kρ{variant} with spin-parity JP = 1+. The cross section for K-p→ Ξ-C+(1.28) with C+ → Kρ{variant} at 4.15 GeV/c incident K- momentum is (6.2 ± 0.6) μb. © 1978.